2022
DOI: 10.3390/computation10020032
|View full text |Cite
|
Sign up to set email alerts
|

On the Conic Convex Approximation to Locate and Size Fixed-Step Capacitor Banks in Distribution Networks

Abstract: The problem of the optimal siting and sizing of fixed-step capacitor banks is studied in this research from the standpoint of convex optimization. This problem is formulated through a mixed-integer nonlinear programming (MINLP) model, in which its binary/integer variables are related to the nodes where the capacitors will be installed. Simultaneously, the continuous variables are mainly associated with the power flow solution. The main contribution of this research is the reformulation of the exact MINLP model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…From Table I, it is also observed that the overall profit obtained in scenario 2 is $11727.012, which is 33.085 % compared to BC. The results achieved by LFM-SOA were compared with other methods in the literature and found that the performance of the proposed method is better compared to other methods discussed in [7]- [10], [15].…”
Section: A Results and Discussion -Ieee 33-bus Test Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…From Table I, it is also observed that the overall profit obtained in scenario 2 is $11727.012, which is 33.085 % compared to BC. The results achieved by LFM-SOA were compared with other methods in the literature and found that the performance of the proposed method is better compared to other methods discussed in [7]- [10], [15].…”
Section: A Results and Discussion -Ieee 33-bus Test Systemmentioning
confidence: 99%
“…The purpose of OCS and AEDNS optimisation in the radial EDN is to maximise the net profit by minimising P Loss, lowering the capacitor investment cost and minimising the DG power purchase cost provided the power balancing and inequality limitations are satisfied. These issues are presented mathematically as stated in (1)- (10).…”
Section: Mathematical Formulations For the Chosen Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of the ref. [21] proposed the application of the second-order cone programming with mixed-integer variables for siting and sizing fixed-step capacitor banks in radial distribution networks to reduce grid power losses under peak load conditions. Numerical simulations including annual grid operating costs under peak load conditions while considering investment costs in capacitor banks showed the effectiveness of the proposed methodology when compared to the exact solution in the GAMS software and some metaheuristic optimizers.…”
Section: State Of the Artmentioning
confidence: 99%